PERAN LEMBAGA KEUANGAN BANK DAN LEMBAGA KEUANGAN BUKAN BANK DALAM MEMBERIKAN DISTRIBUSI KEADILAN BAGI MASYARAKAT - Jamal Wiwoho (Masalah-Masalah Hukum, 2014)
Financial institutions is expected to provide justice for the distribution. Formulation of the problem that researchers ask is how the role of banks financial institutions and non-bank in providing public justice and the factors driving the increased role of banks and financial institutions non-bank in providing the distribution of public justice. The result of the research are 1). The role of financial institutions are: raise public funds; channelling funds society; transfer of assets; liquidity; allocation of income;. transaction. 2). Factors that encourage an increased role of financial institutions in providing the distribution of public justice, among others: increase amount of income of the middle class families and individuals with sufficient incomes, especially among the middle and have a portion of income for savings each year; rapid development of industry and technology.